Ternary and quaternary sustainable cementitious composites containing rice husk ash: a comprehensive review - Yi Jing; Jin Chai Lee; Wei Chek Moon; Yong Jin; Jing Lin Ng; Ming Kun Yew (Discover Applied Sciences, 2025)
Abstract The direct CO2 emissions of the cement production industry have increased significantly, accounting for approximately 7% of the CO2 emissions. Rice husk ash (RHA), an agricultural byproduct, has gained substantial interest as a commonly used supplementary cementitious materials (SCMs) and shows potential application in concrete. This study comprehensively examines existing literature on ternary and quaternary cementitious composites mixed with RHA, providing a detailed overview of their mechanical properties, durability, and CO2 emissions. Analysis shows that the use of combinations of RHA and other materials as SCMs improves the mechanical and durability properties of cementitious composites and reduces CO2 emissions during concrete production when compared with that of replacing aggregates. Specifically, the synergistic use of RHA and olive waste ash increases compressive strength by 58.7%, and the synergistic use of RHA and steel fiber increases flexural strength by 78.4%. The combination of RHA, steel fiber, and waste marble powder increases splitting tensile strength by 96.5%, and the synergistic use of RHA and bacteria increases water absorption resistance by 69% and chloride resistance by 83%. The combination of RHA and bacteria increases permeability resistance by 83%. Furthermore, the synergistic use of RHA and nano-CuO also increases permeability resistance by 51.88%. Finally, the synergistic use of RHA and fly ash achieves the optimal reduction in CO2 emissions. Consequently, considering the challenges of global warming and climate change, this comprehensive review can be a reference for further exploring the utilization of RHA in building materials.